Polysaccharide-based electroconductive films for controlled release of ciprofloxacin - AYCAN, DİDEM; ALEMDAR YAYLA, NESLİHAN (My University, 2022)
Hereby, fabrication of hyaluronic acid/gelatin/sodium alginate (HA/Gel/SA) polymeric films, which contain electroconductive poly(3,4ethylenedioxythiophene)/poly(styrenesulfonate) (PEDOT:PSS) particles, is studied for drug release applications. The characterization of synthesized PEDOT:PSS and HA/Gel/SA-(PEDOT:PSS) films is verified by using FT-IR and RAMAN spectroscopy. Conductivity values of the films containing 0, 4, and 6% v/v PEDOT:PSS are found via a four-point probe technique to determine the optimum composition of the films for the targeted field. Additionally, swelling, mechanical, and cytotoxicity tests are carried out according to the related methods. Ciprofloxacin (CIP), which is a commonly used antibiotic, is loaded into the polymeric matrix and its release behavior is investigated. All results indicate that the incorporation of PEDOT:PSS increases the mechanical performance and decreases the burst release of drug resulted in more sustained release profile. The HA/Gel/SA-(PEDOT: PSS) formulation is clearly a promising drug carrier that also supports cell viability due to its high cytocompatibility.
Keywords: Kimya; Fizikokimya; Polimer Karakterizasyonu; Temel Bilimler; Chemistry; Physical Chemistry; Characterization of Polymers; Natural Sciences; POLİMER BİLİMİ; Temel Bilimler (SCI); POLYMER SCIENCE; CHEMISTRY; Natural Sciences (SCI); Polimerler ve Plastikler; Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Polymers and Plastics; Chemistry (miscellaneous); General Chemistry; Physical Sciences; conducting polymers; drug delivery systems; polysaccharides; HYALURONIC-ACID HYDROGELS; CONDUCTING POLYMERS; DRUG-DELIVERY; MECHANICALLY ROBUST; COMPOSITE FILM; BONE ASH; CHITOSAN; FABRICATION; GELATIN; PROTEIN; conducting polymers; drug delivery systems; polysaccharides